Respons Pertumbuhan Dan Produksi Tanaman Kacang Tanah (Arachis hypogaea L.) Terhadap Pemberian Paclobutrazol Dan Pupuk Kalium - Jonis Ginting; Mariati Mariati (Universitas Sumatera Utara, 2014)
The purpose of the study was to determine the effect of paclobutrazol and potassium fertilizer onthe growth and yield of peanuts. The research was conducted at Pasar I Tanjung Sari street, Medanwith the height of 25 metres above sea level, began from May until October 2013. The research wasarranged with a randomized block design with two factors. The first factor was concentration ofpaclobutrazol ( 0 ; 75 ppm ; 150 ppm and 225 ppm ) and the second was dose of KCl ( 0; 0.15 g ;0.3 g and 0.45 g ) . The parameters observed were plant height, number of ginofor, number ofproductive branches, number of unproductive branches, days to flowering, harvesting, pod weightper sample, number of filled pods per sample, number of empty pods per sample, weight of grainper sample, weight of grain per plot and weight of 100 grains. The results showed that plant height,number of ginofor, number of productive branches, days to flowering, pod weight per sample,number of filled pods per sample, weight of grain per sample, weight of grain per plot, and weightof 100 grains were significantly affected by paclobutrazol concentration. However all parametersobserved were unsignificantly affected by dose of KCl. There was also no interaction betweenpaclobutrazol concentration and dose of KCl .Key words : peanuts , paclobutrazol , KCl fertilizer.